Using dramatic activities in teaching language forms and functions for form 4 - Chong, Ina Ching Phin (Universiti Malaysia Sarawak, UNIMAS, 2003)
This project is undertaken to identify the strengths and difficulties in using dramatic activities in teaching Language Forms and Functions for Form 4. A study was conducted in SMK St Mary Kuching.